2016
DOI: 10.1186/s12888-016-0909-3
|View full text |Cite
|
Sign up to set email alerts
|

Nonmedical use of prescription drugs in the European Union

Abstract: BackgroundNonmedical prescription drug use (NMPDU) refers to the self-treatment of a medical condition using medication without a prescriber’s authorization as well as use to achieve euphoric states. This article reports data from a cross-national investigation of NMPDU in five European Countries, with the aim to understand the prevalence and characteristics of those engaging in NMPDU across the EU.MethodsA parallel series of self-administered, cross-sectional, general population surveys were conducted in 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
127
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(141 citation statements)
references
References 33 publications
(28 reference statements)
9
127
1
4
Order By: Relevance
“…However, the associated social and economic impact of opioid abuse, addiction and overdoses are shifting how physicians approach pain control in the operating room. Opioid misuse is a leading public health concern in the United States (Kolodny et al, ; Rudd et al, ), and trends of increasing opioid abuse and overdoses are developing in the European Union (Novak et al, ). In the United Kingdom, opioid prescriptions rose 58% between 2000 and 2010 (Zin et al, ) and within this time frame, an increase in opioid‐related deaths was also identified (Giraudon et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the associated social and economic impact of opioid abuse, addiction and overdoses are shifting how physicians approach pain control in the operating room. Opioid misuse is a leading public health concern in the United States (Kolodny et al, ; Rudd et al, ), and trends of increasing opioid abuse and overdoses are developing in the European Union (Novak et al, ). In the United Kingdom, opioid prescriptions rose 58% between 2000 and 2010 (Zin et al, ) and within this time frame, an increase in opioid‐related deaths was also identified (Giraudon et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Methadone injecting and its diversion from therapeutic use is a common problem in connection with opiate substitution therapy. 13,[21][22][23] However, no other studies in Hungary have shown such a high prevalence of methadone injection as suggested by our results. As a matter of fact, methadone is almost invisible in data reported by needle and syringe programmes' clients.…”
Section: Hungarymentioning
confidence: 57%
“…A novel finding of our study is the relatively high (16%) prevalence of methadone among the compound cases. Methadone injecting and its diversion from therapeutic use is a common problem in connection with opiate substitution therapy . However, no other studies in Hungary have shown such a high prevalence of methadone injection as suggested by our results.…”
Section: Resultsmentioning
confidence: 99%
“…[1,2] Current pain management relies on nonsteroidal anti-inflammatory drugs (NSAIDs) and opioids. [5][6][7] In contrast, κ-opioid receptor agonists lack the abuse potential of μ-opioids, which made them promising candidates for pain treatment. [3,4] Opioids are the strongest painkillers, which exert their action via three types of opioid receptors, μ, δ, and κ.…”
Section: Introductionmentioning
confidence: 99%
“…However, in addition to pain relief, they produce side effects such as sedation, constipation, respiratory depression, euphoria, misuse, and addiction, which resulted in the opioid crisis. [5][6][7] In contrast, κ-opioid receptor agonists lack the abuse potential of μ-opioids, which made them promising candidates for pain treatment. A prototypic κ-receptor selective agonist is U50,488H (U50), which has been shown to exert effective analgesia in animal pain models.…”
Section: Introductionmentioning
confidence: 99%